2013
DOI: 10.1371/journal.pone.0080067
|View full text |Cite
|
Sign up to set email alerts
|

Profound Effects of Population Density on Fitness-Related Traits in an Invasive Freshwater Snail

Abstract: Population density can profoundly influence fitness-related traits and population dynamics, and density dependence plays a key role in many prominent ecological and evolutionary hypotheses. Here, we evaluated how individual-level changes in population density affect growth rate and embryo production early in reproductive maturity in two different asexual lineages of Potamopyrgus antipodarum, a New Zealand freshwater snail that is an important model system for ecotoxicology and the evolution of sexual reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…2013a), temperature (Dybdahl and Kane 2005), and population density (Neiman et al. 2013a; Zachar and Neiman 2013) suggest that at least some of the genetic variation for growth rate observed in benign laboratory conditions may be suppressed or expressed differently in the more heterogeneous natural populations. Indirect support for this possibility is provided by Neiman et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2013a), temperature (Dybdahl and Kane 2005), and population density (Neiman et al. 2013a; Zachar and Neiman 2013) suggest that at least some of the genetic variation for growth rate observed in benign laboratory conditions may be suppressed or expressed differently in the more heterogeneous natural populations. Indirect support for this possibility is provided by Neiman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Because a higher growth rate likely translates into fitness advantages (earlier reproduction) for female P. antipodarum (also see Tibbets et al 2010), our results raise the questions of why there exists substantial genetic variation for this trait in P. antipodarum and why sexual P. antipodarum grow and mature relatively slowly. With respect to the maintenance of genetic variation for growth rate, the well-documented dependence of growth rate in P. antipodarum on environmental variables like food quality (Neiman et al 2013c;Krist et al 2014), food quantity (Neiman et al 2013a), temperature (Dybdahl and Kane 2005), and population density (Neiman et al 2013a;Zachar and Neiman 2013) suggest that at least some of the genetic variation for growth rate observed in benign laboratory conditions may be suppressed or expressed differently in the more heterogeneous natural populations. Indirect support for this possibility is provided by Neiman et al (2013c), who found that the growth rate advantages experienced by tetraploid versus triploid P. antipodarum when fed a high-phosphorus diet (notably, a diet higher in phosphorus than the snails in the present study received) disappear under relatively low-P conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spirulina algae three times per week, as previously described 62 . We arbitrarily selected adult 114 snails from lake collections (each of which consisted of hundreds to thousands of individuals) 115 and isolated each snail in a 0.5 L glass container with 300ml carbon-filtered H 2 O.…”
Section: Materials and Methods 105mentioning
confidence: 99%